2009
DOI: 10.1007/s10803-008-0684-1
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Information Processing Speed is Intact in Autism but not Correlated with Measured Intelligence

Abstract: Speed of information processing, as measured by inspection time (IT), is a robust predictor of intellectual functioning. However, among individuals with autism and low IQ scores, IT has been reported to be discrepantly fast, and equal to that of high IQ typically developing children (Scheuffgen et al. in Dev Psychopathol 12: 83-90, 2000). The present investigation replicates and extends this study by examining IT and its relationship to IQ in a higher functioning (average range mean IQ) group of children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 22 publications
4
36
2
Order By: Relevance
“…Indeed, only when their general intelligence was underestimated using Wechsler IQ did the autistic subgroup show a significant IT advantage. Our results confirm previous autism spectrum IT findings (e.g., Scheuffgen et al, 2000;Wallace, Anderson, et al, 2009) but allow for a more nuanced interpretation. Groups consisting primarily of autistics should perform better on IT than their Wechsler FSIQ scores predict.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, only when their general intelligence was underestimated using Wechsler IQ did the autistic subgroup show a significant IT advantage. Our results confirm previous autism spectrum IT findings (e.g., Scheuffgen et al, 2000;Wallace, Anderson, et al, 2009) but allow for a more nuanced interpretation. Groups consisting primarily of autistics should perform better on IT than their Wechsler FSIQ scores predict.…”
Section: Discussionsupporting
confidence: 91%
“…The ASD group’s processing speed was comparable to that of a group of typically developing control (TDC) children with IQ scores 25 points higher, on average. The two most recent studies using the IT task extend these results finding comparable processing speed between: 1) a group of relatively high-functioning children with ASD and age and IQ matched TDC children (Wallace, Anderson, & Happé, 2009) and 2) an adult savant with ASD and a control group of neurotypical adults matched on age and verbal ability (Wallace, Happé, & Giedd, 2009). …”
Section: Introductionmentioning
confidence: 66%
“…In fact, when compared to typically developing children, children with autism have commonly been found to perform poorly on measures of processing speed (Calhoun and Mayes 2005;Mayes and Calhoun 2003, 2004. While some studies have reported a processing speed advantage for individuals with autism relative to that expected from their levels of IQ, these findings are more consistent with intact speed of processing (i.e., speed of processing equivalent to controls), rather than a speed of processing advantage (Scheuffgen et al 2000;Wallace et al 2009). …”
Section: Discussionmentioning
confidence: 99%